The Induction of IL-33 in the Sinus Epithelium and Its Influence on T-Helper Cell Responses - AKKOÇ, TUNÇ (PUBLIC LIBRARY SCIENCE, 2015)
Background Chronic rhinosinusitis (CRS) is characterized by epithelial activation and chronic T-cell infiltration in sinonasal mucosa and nasal polyps. IL-33 is a new cytokine of the IL-1 cytokine family that has a pro-inflammatory and Th2 type cytokine induction property. The role of IL-33 in the pathomechanisms of CRS and its interaction with other T cell subsets remain to be fully understood. Methods The main trigger for IL-33 mRNA expression in primary human sinonasal epithelial cells was determined in multiple cytokine and T-cell stimulated cultures. The effects of IL-33 on naive, Th0 and memory T-cells was studied by PCR, ELISA and flow cytometry. Biopsies from sinus tissue were analyzed by PCR and immunofluorescence for the presence of different cytokines and receptors with a special focus on IL-33. Results IL-33 was mainly induced by IFN-gamma in primary sinonasal epithelial cells, and induced a typical CRSwNP Th2 favoring cytokine profile upon co-culture with T-helper cell subsets. IL-33 and its receptor ST2 were highly expressed in the inflamed epithelial tissue of CRS patients. While IL-33 was significantly up-regulated in the epithelium for CRSsNP, its receptor was higher expressed in sinus tissue from CRSwNP. Conclusions production, which could both contribute to a further increase of an established Th2 profile in CRSwNP.The present study delineates the influence of IL-33 in upper airway epithelium and a potential role of IL-33 in chronic inflammation of CRSwNP by enhancing Th2 type cytokine
Keywords: IMPORTANT RESEARCH QUESTIONS; INNATE LYMPHOID-CELLS; CHRONIC RHINOSINUSITIS; EXPRESSION; INFLAMMATION; ALLERGY; ASTHMA; SUPPRESSION; ENDOTYPES; DIAGNOSIS